Primary peritoneal mucinous cystadenocarcinoma mimicking possible recurrent ovarian mucinous cystadenoma: coincidental pathology or a spectrum of disease?. Issue 7 (13th July 2021) - Filippini, Claire; Smyth, Sarah; Soleymani Majd, Hooman; Johnson, Catherine
Abstract : We present the case of a 32-year-old woman with a previous surgical history of benign mucinous cystadenoma resected in 2012 who underwent magnetic resonance cholangiopancreatography following her second pregnancy in 2020. This demonstrated a large cystic mass in the left subdiaphragmatic space. Histopathology confirmed a well-differentiated primary peritoneal mucinous cystadenocarcinoma displaying cells of a Mullerian origin. We subsequently discuss the aetiology of these conditions separately and explore the possibility of a connection between the two regarding origin or potential malignant transformation that may otherwise have occurred coincidentally in this young patient. We also acknowledge a paucity of evidence regarding subsequent management strategies.